Was Gerschenkron right? Bulgarian agricultural growth during the Interwar period in light of modern development economics - Michael Kopsidis; Martin Ivanov (European Historical Economics Society (EHES), 2015)
The classical view of Bulgaria's failed industrialization prior to the Second World War was established by Alexander Gerschenkron. According to his interpretation, an inherently backward small peasant agriculture and well-organized peasantry not only retarded growth in agriculture but obstructed any possible industrialization strategy. Following Hayami and Ruttan, we utilize the decomposition of farm labor productivity into land productivity, and land-to-man ratio to analyze the sources of growth in Bulgaria's agriculture 1887-1939. Our results show that Bulgaria's peasants did cross the threshold to modern growth during the Interwar period. Rich qualitative evidence supports the findings of our quantitative analysis that contrary to Gerschenkron's view and conventional wisdom, Bulgaria's peasants substantially contributed to the modernization of Bulgaria's economy and society. We interpret our results in light of modern development economics, and conclude that agriculture formed no impediment to Bulgaria's industrialization. The reasons that a 'large industrial spurt' did not occur in Bulgaria until 1945 are not to be found in the agricultural sector.
Keywords: N53; N54; N13; N14; O13; 330; Bulgaria; agricultural productivity; peasant agriculture; industrialization